Formulation Design and Functional Characterisation of a Novel Vaginal Mucosal Drug Delivery System - Ahmed S. A. M. Alzainy; Joshua S Boateng (University of Huddersfield Press, 2022)
The aim of this research was the development, characterisation, and optimisation of composite polymer-based formulations for vaginal drug delivery using metronidazole (MTz) as a model drug to treat bacterial infection in the vagina. Blank (BLK) composite wafers comprising carrageenan (CARR) and sodium alginate (SA) were initially formulated and tested. However, due to poor physico-chemical properties, further formulations were developed involving combination of carbopol (CARB)with SA or CARB with CARR, modified with hydroxypropylmethyl cellulose (HPMC)in different weight ratios and plasticised with polyethylene glycol (PEG 200).Drug loaded (DL) wafers were obtained by loading selected optimised composite CARB-CARR or CARR-SA based gels with 0.75% of MTz prior to freeze-drying. Formulations were characterised using texture analyser (hardness, mucoadhesion), scanning electron microscopy (SEM), X-ray diffractometry (XRD), swelling capacity and in vitro drug dissolution study using HPLC.